2008
DOI: 10.1021/ic8011958
|View full text |Cite
|
Sign up to set email alerts
|

Four-Coordinate Mo(II) as (silox)2Mo(PMe3)2and Its W(IV) Congener (silox)2HW(η2-CH2PMe2)(PMe3) (silox =tBu3SiO)

Abstract: The reduction of [( t Bu3SiO)2MoCl]2 (2 2) provided the cyclometalated derivative, (silox)2HMoMo(κ-O,C-OSi t Bu2CMe2CH2)(silox) (3), and alkylation of 2 2 with MeMgBr afforded [( t Bu3SiO)2MoCH3]2 (4 2). The hydrogenation of 4 2 was ineffective, but the reduction of 2 2 under H2 generated [( t Bu3SiO)2MoH]2 (5 2), and the addition of 2-butyne to 3 gave [(silox)2Mo]2(μ:η2η2-C2Me2) (6), thereby implicating the existence of [(silox)2Mo]2 (1 2). The addition of (silox)H to Mo(NMe2)4 led to (silox)2Mo(NMe2)2 (7), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…This high reactivity towards N 2 reduction is unusual for an octahedral Mo( iii ) complex, and highlights the particularity of the TBOS ligand, which can adopt mono- or bidentate binding modes while being relatively small compared to larger siloxy ( e.g. t Bu 3 SiO)19 or N( t Bu) (3,5-Me 2 C 6 H 3 ) ligands 7 g…”
Section: Resultsmentioning
confidence: 90%
“…This high reactivity towards N 2 reduction is unusual for an octahedral Mo( iii ) complex, and highlights the particularity of the TBOS ligand, which can adopt mono- or bidentate binding modes while being relatively small compared to larger siloxy ( e.g. t Bu 3 SiO)19 or N( t Bu) (3,5-Me 2 C 6 H 3 ) ligands 7 g…”
Section: Resultsmentioning
confidence: 90%
“…As Figure indicates, activation energy calculations of 1,2-MeH-elimination are generally in line with the experimentally determined, directly or indirectly, data of MeH loss from the XY­( t Bu 3 SiNH)­MMe systems, although they err to the high side. Although calculations suggested that 1,2-MeH-elimination from ( t Bu 3 SiNH)­( t Bu 3 SiN) 2 WMe ( 12 -Me) was prohibitive at Δ H ⧧ elim = 61.6 kcal/mol, the tungsten system was still interesting due to a significant enthalpy of methane binding of −15.6 kcal/mol to ( t Bu 3 SiN) 3 W ( 13 ); even the free energy of MeH binding was favorable at Δ G ° bind = −8.4 kcal/mol. ,, Three-coordinate imido species were also pyramidalized in the second and third rows in groups 5 and 6 due to n d z 2 /( n + 1)­p/( n + 1)­s mixing, a geometric distortion favorable toward binding.…”
Section: The Tutorialmentioning
confidence: 99%
“…To date, isolable examples of three-coordinate M(N[R]Ar) 3 complexes are known only for M = Ti, V, Cr, , and Mo; also, a uranium analogue has been isolated as its THF adduct . While the reactivity of trivalent M(N[R]Ar) 3 complexes of different periodic groups depends greatly on the d n count, reactivity differences displayed by metals of the same group are governed by a less intuitive set of properties. This point is highlighted by Mo(N[ t -Bu]Ar) 3 , which readily effects the reductive cleavage of the dinitrogen molecule, while its Cr analogue, Cr(N[ t -Bu]Ar) 3 , is unreactive toward N 2 under similar conditions . Accordingly, the discovery of new paradigms in small-molecule reactivity stemming from M(N[R]Ar) 3 complexes has fueled our quest to expand the library of known variants throughout the early transition elements.…”
Section: Introductionmentioning
confidence: 99%
“…( greatly on the d n count, reactivity differences displayed by metals of the same group are governed by a less intuitive set of properties. [21][22][23][24] This point is highlighted by Mo(N[t-Bu]Ar) 3 , which readily effects the reductive cleavage of the dinitrogen molecule, 4-7 while its Cr analogue, Cr(N[t-Bu]Ar) 3 , is unreactive toward N 2 under similar conditions. 18 Accordingly, the discovery of new paradigms in small-molecule reactivity stemming from M(N[R]Ar) 3 complexes has fueled our quest to expand the library of known variants throughout the early transition elements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation